Adoption of green methodology in industry for the synthesis of Sildenafil citrate & Celecoxib: A case study. (2022) - Saxena, Nisha; Srivastav, Noopur; Kumar, Amar; Anjali, Anupama
Graphical abstract: Highlights: The discussed improved method includes alteration in the synthetic strategy for increasing the overall yield of the drug and development of green efficient purification technique. Little change in chemistry via understanding the mechanistic paths reduces the formation of impurities in sildenafil citrate and celecoxib synthesis makes the process greener. Along with this the new strategies adopted use of green solvents in the final steps of for drug preparation. The specified advantage of use of green solvents is to minimize the residues remaining in the API synthesized. Abstract: Medicines are the imperative constituent in the present day lifestyle and their consumption for different cause's increases day by day. Synthesis of most of the drugs involves use of toxic chemicals and hazardous solvents, tedious workup or lengthy strategies. The needs of environment friendly procedures are the prerequisites of current environment concern. The known drug candidates Sildenafil citrate and Celecoxib are selected for the investigation and study for improved synthetic opportunities. It is found that several alterations are useful in the synthesis of these biological active profiles and they are adopted for large scale production of the compound in pharmaceutical industries. The old and new synthetic strategies are discussed in this case study based article.